Didn't Plan One But Got One: Unintended and Sooner-Than-Intended Births among Men and Women in Six European Countries - Zuzanna Brzozowska; Isabella Buber-Ennser; Bernhard Riederer; Michaela Potančoková (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2018)
This article examines the characteristics of women and men who got a child despite declaring no such wish up to three years before the pregnancy. We compare these unintended or sooner-than-intended parents with those who got a child as intended and those who, in line with their intentions, did not increase their family size. Using the first and second wave of the Generations and Gender Survey for six low-fertility countries (Austria, Bulgaria, France, Hungary, Italy and Poland) we conduct bivariate analysis and (multinomial) logit models. Our results show that not realising negative fertility intentions is linked more to a particular stage in one's life course and finding a new partner than to a disadvantaged socio-economic status. Thus, most of the unintended or sooner-than-intended births are probably neither unintended nor sooner-than-intended, but are a result of change in one's life circumstances between the time of measuring the fertility intentions and their realisation.
Keywords: 300; Fertility intentions; realisation of fertility intentions; unintended births; sooner-than-intended births